2017
DOI: 10.1021/acscatal.7b02915
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective Semihydrogenation of Alkynes to Alkenes by Using an Unsupported Nanoporous Palladium Catalyst: No Leaching of Palladium into the Reaction Mixture

Abstract: We report the highly chemoselective and stereoselective semihydrogenation of alkynes to Z-internal and terminal alkenes by using unsupported nanoporous palladium (PdNPore) as a heterogeneous catalyst under mild reaction conditions (room temperature and 1 atm of H2). The semihydrogenation of various terminal/internal and aromatic/aliphatic alkynes afforded the corresponding alkenes in good chemical yields with high selectivities. PdNPore further showed high chemoselectivity toward terminal alkynes in the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(47 citation statements)
references
References 53 publications
1
43
0
3
Order By: Relevance
“…Lu et al. demonstrated that PdNPore prepared from an AuAl alloy was a highly chemo‐ and stereroselective catalyst for the H 2 semihydrogenation of alkynes to alkenes at room temperature (Scheme a) . It was noted that the combination of PdNPore (5 mol %) with NaOH (1 equiv) under 1 atm of H 2 in EtOH is crucial for suppressing the formation of ( E )‐alkenes ( 8′ ) and over‐reduced alkanes ( 8′′ ).…”
Section: Nanoporous Pd Catalysismentioning
confidence: 99%
See 1 more Smart Citation
“…Lu et al. demonstrated that PdNPore prepared from an AuAl alloy was a highly chemo‐ and stereroselective catalyst for the H 2 semihydrogenation of alkynes to alkenes at room temperature (Scheme a) . It was noted that the combination of PdNPore (5 mol %) with NaOH (1 equiv) under 1 atm of H 2 in EtOH is crucial for suppressing the formation of ( E )‐alkenes ( 8′ ) and over‐reduced alkanes ( 8′′ ).…”
Section: Nanoporous Pd Catalysismentioning
confidence: 99%
“…Solid Pd catalysts are generally employed in the highly efficient semihydrogenation of alkynes using H 2 gas, but they often lead to over-reduction to alkane, partial isomerization of (Z)alkene to (E)-alkene, and serious leachingo fP d. [22a,b] Lu et al demonstrated that PdNPore prepared from an AuAl alloy was ah ighly chemo-and stereroselective catalystf or the H 2 semihydrogenation of alkynes to alkenesa tr oom temperature (Scheme 29 a). [53] It was noted that the combination of PdNPore (5 mol %) with NaOH (1 equiv) under 1atm of H 2 in EtOH is crucial for suppressing the formation of (E)-alkenes (8')a nd over-reduced alkanes (8''). Interestingly,P dNPore showedh igh chemoselectivity for the semihydrogenation of terminal alkynes in the presence of internal alkynes( Scheme 29 b).…”
Section: Semihydrogenation Of Alkynesmentioning
confidence: 99%
“…In addition, Pd is known for its high selectivity for some heterogeneous (e.g., the hydrogenation of acetylene) and homogeneous catalytic reactions (e.g., Suzuki reaction, Sonogashira reaction, etc.). The high catalytic performance of Pd for these reactions renders them highly promising for many applications, such as fuel cells, pharmaceutical, automotive (catalytic converters), and electrochemical sensors . In recent years, Pd has gained increasing attention as a substitute for Pt in many electrocatalytic applications.…”
Section: Introductionmentioning
confidence: 99%
“…However, this catalytic system requires 1) lead (Pb) to suppress the activity of a palladium (Pd) catalyst, 2) quinoline for the same purpose and 3) hydrogen (H 2 ) gas as a hydrogen (electron (e − ) and proton (H + )) source. Recently, excellent catalytic systems for semihydrogenation of alkynes have been developed …”
Section: Introductionmentioning
confidence: 99%
“…Recently, excellent catalytic systems for semihydrogenation of alkynes have been developed. [3][4][5][6][7][8][9][10] A TiO 2 photocatalyst generates positive holes in the valence band and electrons in the conduction band by irradiation of UV light and these cause oxidation and reduction, respectively.…”
Section: Introductionmentioning
confidence: 99%